Historical background of the reform of the criminal process in Paraguay (Legal journal - Research in Legal and Social Sciences, 2017)
The sanction of the new Code of Criminal Procedure in July 1998, Law 1286, was the result of hard work aimed at overcoming the inquisitorial procedure characterized by the violation of the rights and guarantees of the people subjected to a judicial process, which prevailed both in Paraguay as in other Latin American countries. The new norm, faithful to the accusatory model, proposes the simplification of the formal requirements, of the procedural acts, as well as greater freedom to obtain the means of proof and access to Justice for all the inhabitants of Paraguay. After long years of immobility and relative isolation lived in Paraguay as a result of its historical circumstances, the idea of ​​reforming the secular Paraguayan criminal procedural legislation, within the framework of the general process of institutional transformations, became essential. As an example of this transformation, it is worth mentioning the procedural guarantees set forth in title I of the Criminal Procedure Code adopted in 1999, which is a literal reflection of the fundamental rights set forth in the National Constitution of 1992, that is, the procedural reform reflects the spirit of the Magna Carta as a coherent and harmonious whole.
Keywords: procedural guarantees; accusatory model; Criminal process; Reform